Effect of number of sprints in an SIT session on change in V.O2max: A meta-analysis - Vollaard, N. B. J.; Metcalfe, R. S.; Williams, S. (Medicine & Science in Sports & Exercise, 2017)
PURPOSE: Recent meta-analyses indicate that sprint interval training (SIT) improves cardiorespiratory fitness (V.O2max), but the effects of various training parameters on the magnitude of the improvement remain unknown. The present meta-analysis examined the modifying effect of the number of sprint repetitions in an SIT session on improvements in V.O2max.